Transcritos relacionados com a maturação oocitária em bovinos: expressão em oócitos de folículos pré-antrais e antrais e efeitos in vitro de EGF e progesterona. - Bezerra, Francisco Taiã Gomes (2020)
During growth, under the influence of hormones and growth factors, such as Progesterone (P4) and Epidermal Growth Factor (EGF), oocytes synthesize large amounts of mRNA that are accumulated to form a large stock of maternal mRNA, are the growth factor and differentiation 9 (GDF9), a cMOS kinase, a specific poly (a) ribonuclease (PARN), the translation initiation factor (eIF4E), a cyclin B1 (CCNB1) and a history with specific oocyte ligand (H1FOO). Thus, the objectives of this study were: (1) to evaluate the levels of mRNA for eIF4E, PARN, H1FOO, cMOS, GDF9 and CCNB1 in oocytes of secondary and antral follicles at different stages of development and (2) to evaluate the factor factor epidermal growth (EGF) and progesterone (P4) without growth, resuming the mean and levels of levels transcribed in oocytes of small and medium antral follicles after pre-maturation and in vitro maturation. For this purpose, fresh oocytes derived from secondary bovine follicles, as well as small, medium and large antral follicles were collected to analyze the levels of mRNA for transcripts mentioned above. In addition, secondary follicles grown for 18 days or the cumulus oocyte complex (CCO) of antral follicles after growth and pre-maturation were also collected for analysis of mRNA levels. Then, the CCOs derived from small and medium antral follicles were cultured in medium containing EGF (10 ng / mL), P4 (100 µM) or both. During cultivation, growth rates were evaluated, taken from the average and levels of mRNA mentioned above. The levels of mRNA in oocytes from secondary and anal follicles were analyzed by the Kruskal-Wallis test. The percentage of oocytes in the VG was analyzed using the Mann Whitney test. The results showed that mRNA levels for H1FOO, GDF9, CCNB1 and PARN were higher in oocytes of small, medium and large antral follicles than in secondary follicle oocytes. The cultivation of secondary follicles in vitro significantly increased the levels of all studied transcripts. Pre-maturation of oocytes from small antral follicles increased the levels of mRNA for GDF9, PARN and eIF4E. In addition, higher levels of cMOS and H1FOO were identified in oocytes from pre-matured middle antral follicles. Additionally, EGF and P4 influenced the growth of oocytes submitted to in vitro prematuration and the expression of transcripts in oocytes of small and medium antral follicles. EGF or P4 also increased cMOS mRNA levels (P <0.05), while both EGF and P4 increased mRNA levels to H1FOO levels. In conclusion, follicular growth is associated with an increase in the expression of H1FOO, GDF9, CCNB1 and PARN. In vitro culture of secondary follicles, pre-maturation and oocyte maturation of antral follicles increase the expression of eIF4E, PARN, H1FOO, cMOS, GDF9 and CCNB1. In addition, P4 alone or associated with EGF increases mRNA expression for cMOS, CCNB1 and H1FOO